(untitled) (Research, Society and Development, 2022)
Biological space is defined by the distance between the alveolar bone crest and the free gingival margin, consisting of distinct regions: sulcus epithelium, junctional epithelium and conjunctival insertion, which together have an average depth of 2.73 mm. From the base of the gingival sulcus to the bone crest, the biological distance is established. Violating this distance is an etiologic factor for periodontal diseases associated with inflammation. Surgical techniques of clinical crown lengthening and orthodontic traction are effective approaches to restore biological distances and minimize the risk of periodontal disease. Among the conditions for planning are excessive gingival exposure when smiling, altered passive tooth eruption, lack of tooth height for rehabilitation, and cavities beyond the gingival sulcus. Thus, the importance of reestablishing, prior to prosthetic rehabilitation, biological distances becomes evident, with procedures that respect the anatomy of the periodontium and minimize the risk of periodontal diseases. This article is the result of an integrative literature review, with a qualitative analysis of works that identified the importance of reestablishing the biological space.